Synthesis of Carbon–Nitrogen–Phosphorous Materials with an Unprecedented High Amount of Phosphorous toward an Efficient Fire‐Retardant Material. Issue 31 (5th July 2018) - Zhang, Wenyao; Barrio, Jesús; Gervais, Christel; Kocjan, Andraž; Yu, Aiping; Wang, Xin; Shalom, Menny
Abstract: Phosphorus incorporation into carbon can greatly modify its chemical, electronic, and thermal stability properties. To date this has been limited to low levels of phosphorus. Now a simple, large‐scale synthesis of carbon–nitrogen–phosphorus (CNP) materials is reported with tunable elemental composition, leading to excellent thermal stability to oxidation and fire‐retardant properties. The synthesis consists of using monomers that are liquid at high temperatures as the reaction precursors. The molten‐state stage leads to good monomer miscibility and enhanced reactivity at high temperatures and formation of CNP materials with up to 32 wt % phosphorus incorporation. The CNP composition and fire‐retardant properties can be tuned by modifying the starting monomers ratio and the final calcination temperature. The CNP materials demonstrate great resistance to oxidation and excellent fire‐retardant properties, with up to 90 % of the materials preserved upon heating to 800 °C in air. Abstract : Dig for fire : A simple, scalable, and straightforward synthesis of carbon–nitrogen–phosphorus (CNP) materials with controllable elemental composition and a large amount of phosphorous (up to 32 %) is presented. These CNP materials exhibit excellent thermal stability to oxidation and great performance as fire‐retardant materials. The best composite retains 90 % of its mass at 800 °C under air.